Steatocystoma Multiplex: “Keep me in your Differentials” - Sudha Sharma; V. Anish Chandran; Praveen Kumar Shukla; Ajay Kumar (Archives of Medicine and Health Sciences)
Steatocystoma multiplex (SM) is a rare autosomal dominant genetic disorder, seen in adolescence and characterized by hamartomatous malformation of the pilosebaceous units. However, sporadic occurrence has been reported in literature. Histopathologic features are characteristic and should be known to the pathologist, to differentiate from other common causes of skin nodules. We report a case of sporadic SM and highlight the characteristic histopathologic features required for diagnosis.